COLOR DESIGNATION AS A MEANS OF EXPRESSION IN MODERN ENGLISH LANGUAGE («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
Color is the most important part of all visual information. It is the color of the clothes of the person you meet, the color of his face, hair, etc. that is remembered first of all.Out of the few available linguistic studies, one can rely on introspection when drawing conclusions: examining the behavior of color terms in contexts through language analysis, the meanings of color definitions are revealed. Color is the subject of many scientific studies. The article is devoted to identifying the peculiarities of the English linguistic picture of the world using the example of colorative phraseological units. The author concludes that the study of colorative phraseological units makes it possible to more clearly understand the peculiarities of the national characters of the English people, the origins and peculiarities of the perception of the picture of the world.
Keywords: black, white, red, color definitions, adjectives, vocabulary, color designation, phraseological unit, cultural linguistics